Caractérisation des aléas littoraux d’érosion et de submersion en Bretagne par l’approche historique - Alain Hénaff; Erwan Le Cornec; Marie Jabbar; Anne Pétré; Jérémy Corfou; Yann Le Drezen; B. van Vliët-Lanoë (Cybergeo, 2018)
Knowledge regarding the systemic vulnerability of coastal territories to erosion and flood has progressed during the last decades thanks to the consideration of hazards but also of other components such as the stakes, the management and the social representations of the coastal risks. However, in numerous cases the development and urbanization of coastal territories submitted to the coastal risks continues. It results in the increase of exposed populations as well as in the increase of the cost of exposed properties, increasing in return their vulnerability. So, in the objective to improve the management strategies and to strengthen the memory of the risk, the need to specify the characteristics of hazards remains important. In this sense, the intensity, the area of distribution and the duration of action of hazards, as well as the magnitude of the forcing and their probability of occurrence require better definition. In this perspective, an approach based on the analysis of hazards of erosion and flooding is led on the coasts of Brittany for the contemporary period, stretching from the end of the 18thcentury to 2010. The data is inventoried from diverse local and regional written and iconographic archives. The intensity, the area of distribution and the duration of (immediate) action are determined from this inventory. The magnitude of the forcing, and consequently the probability of occurrence of these hazards by level of magnitude is more delicate to define. The magnitude, or, more exactly, the size (or severity) cannot depend on the level of the impacts even though we rarely have quantified data through historical data. Thus, an evaluation of the magnitude is proposed by taking into account, for every hazard identified regionally, the diversity of the impacts and the diversity of the forcing which generated it. The results show that they follow a power law which confirms, as for diverse hazards, the existence of a link between size and frequency of these hazards. The probability of occurrence can be computed to specify the annual, the ten-year or the centennial hazards for the region and also the associated uncertainties. These five main characters being specified and quantified, a comparison of hazards over time becomes possible. Most importantly, they become usable to establish a regional “memory” of coastal hazards. Their future evolution could also be monitored within the framework of a future observatory of coastal risks.